# limit x tends to infinity ln((+/x))*-x

*print*Print*list*Cite

### 1 Answer

The request of the problem is vague, hence if you need to solve the limit `lim_(x->oo) (ln x)*(-x), ` hence, you need to substitute `oo` for x in equation such that:

`lim_(x->oo) (ln x)*(-x) = (ln oo)*(-oo) = oo*(-oo)`

`lim_(x->oo) (ln x)*(-x) = -oo`

If you need to solve the limit `lim_(x->oo) (ln (x*(-x)), ` hence, you need to use logarithmic identity such that:

`ln(a*b) = ln a + ln b`

Reasoning by analogy yields:

`lim_(x->oo) (ln (x*(-x)) = lim_(x->oo) (ln x + ln(-x))`

Notice that the logarithm `ln(-x)` is invalid for x>0, hence, the limit cannot be evaluated.

**Hence, evaluating the limit `lim_(x->oo) (ln x)*(-x)` yields `lim_(x->oo) (ln x)*(-x) = -oo.` **